The craniovertebral junction extramedullar tumors. Diagnostics and treatment - Trosh, R. M.; Fedirko, V. O.; Buryk, V. M.; Onishchenko, P. M. (Ukrainian Neurosurgical Journal, 2005)
Article is devoted to diagnostics and treatment features of craniovertebral junction (CVJ) extramedullar tumors. Alongside with a brief historical statement of a problem, the basic attention is given to modern methods of surgical treatment, in particular, to lateral approaches to area СVJ. The necessity of effective preoperative diagnostics and application of the expanded lateral approaches are proved, that essentially improves the nearest and follow-up surgical interventions results.